Variability of phytoplankton communities in central east Atlantic (ESTOC) - Vega-Moreno, D.; Llerandi-García, C.; Cianca, A.; Cardona, L.; Villagarcía, M.; Santana, R.; Rueda, M. J.; Llinas, O. (OCEANS 2011 IEEE - Spain, 2011)
Phytoplankton pigment composition has been studied during two years at station located in the subtropical North Atlantic Ocean, in a station for time series in the ocean. The concentration and proportion of several diagnostic pigments is used for the determination of phytoplankton communities present in the area, and consequently their seasonal and temporal variability. The knowledge of phytoplankton composition in large temporal series is crucial for a better understanding of biogeochemical cycles and for the improvement of the existent chlorophyll data on the series.